2013
DOI: 10.1002/ajh.23443
|View full text |Cite
|
Sign up to set email alerts
|

The hematopoietic cell transplantation‐specific comorbidity index (HCT‐CI) is an outcome predictor for partially matched related donor transplantation

Abstract: To validate the predictive ability of the Hematopoietic Cell Transplantation-Specific Comorbidity Index (HCT-CI) on the outcome of hematopoietic stem cell transplantation (HSCT) patients who received transplants from partially matched related donors (PMRD), a total of 526 patients who received PMRD HSCT between January 2006 and December 2009 at the Institute of Hematology, Peking University were enrolled. Patients were grouped according to their HCT-CI score; 31.0%, 31.4%, and 37.6% of patients had HCT-CI scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 44 publications
1
21
3
Order By: Relevance
“…In the present study, an HCT-CI score of 3 had a trend of increasing NRM and was an independent risk factor for worse survival, which is in keeping with previous studies. 31,32 Our results confirmed that HCT-CI might be a useful tool to assess risk and guide counseling in Ph-negative ALL CR1 patients who are in need of haplo-HSCT. However, the ratio of patients with HCT-CI scores of 3 was comparable between lowand high-risk groups, which suggests that pre-HSCT comorbidity burden was comparable between the groups in this study.…”
supporting
confidence: 73%
“…In the present study, an HCT-CI score of 3 had a trend of increasing NRM and was an independent risk factor for worse survival, which is in keeping with previous studies. 31,32 Our results confirmed that HCT-CI might be a useful tool to assess risk and guide counseling in Ph-negative ALL CR1 patients who are in need of haplo-HSCT. However, the ratio of patients with HCT-CI scores of 3 was comparable between lowand high-risk groups, which suggests that pre-HSCT comorbidity burden was comparable between the groups in this study.…”
supporting
confidence: 73%
“…Second, we confirmed that pre-HSCT comorbidities strongly predicted NRM after haplo-HSCT. 29 However, the ratio of patients with hematopoietic cell transplantation-specific comorbidity index scores of ⩾ 3 was comparable between the cGVHD and non-cGVHD groups, which suggested that the pre-HSCT comorbidity burden was comparable between the groups in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Second, based on our previous study, the haematopoietic cell transplantation-specific comorbidity index (HCT-CI) can also predict outcomes after unmanipulated HBMT. 34 Barba et al 35 suggest that combined HCT-CI and EBMT risk score can better stratify high-risk patients undergoing reduced toxicity allo-HSCT. In our transplantation system, whether the haplo-EBMT risk score and the HCT-CI can be combined to predict outcomes is still unknown, and the methods necessary to properly use these indexes to better stratify patients undergoing haploidentical HSCT require further research.…”
Section: Discussionmentioning
confidence: 99%